The Impact of a Peer-Led Islamic Moderation Program on Mental Well-being and Violent Extremism Prevention among Indonesian Students - Budiman Budiman; Anwar Habibi Siregar; Diva Nada Rizki Nuzlan; Apriliani Apriliani; Putra Apriadi Siregar; Muhammad Rezebri; Cynthia Zebua (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Introduction: Violent extremism among students is a problem that must be addressed, and religious moderation programs are expected to be one effective intervention in improving psychological resilience. This study aims to evaluate the impact of religious moderation education on enhancing religious moderation among university students, with a focus on changes in national commitment, religious knowledge, tolerance, and anti-violent understanding. Method: This study employed a quantitative approach with a single-group pretest-posttest design and was conducted in a province in Indonesia from June to November 2024. The research participants consisted of 39 students involved in a religious moderation education intervention program. Data were collected through a structured questionnaire focusing on four main indicators of religious moderation. The data were then analyzed using a paired sample t-test with JASP version 19. Results: Findings showed a statistically significant increase in all variables after the intervention. National commitment increased from 27.15 to 31.82 (p < 0.001); religious knowledge from 30.33 to 31.95 (p = 0.008); tolerance from 32.69 to 34.10 (p = 0.032); and understanding of anti-violence from 34.10 to 35.79 (p = 0.020). Conclusion: Structured religious moderation education can enhance students' religious moderation by integrating Islamic identity and national responsibility.  Keywords: Religious Moderation; Psychological Resilience; Islamic Education; Extremism; Mental Health